Problematic English Consonant Sounds for Indonesian EFL Learners - Regina Putri Wahyu Anjani; Hanna Irma Wahyuni Wahyuni; Maria Paskalia Putri Nugraheni; Barli Bram Barli Bram (Journey: Journal of English Language and Pedagogy, 2023)
This paper analyzes Indonesian EFL learners' perspectives onpronouncing problematic English consonant sounds. Therefore, the opinions of the Indonesian EFL learners about the difficulty level of 24 problematic consonants were the expected data. A descriptivequalitative method was used to analyze the data of this study. The study reveals that interlingual, intralingual, and developmental factors influence problematic English consonant sounds like /z/, /ʃ/, /ʒ/, /tʃ/, /ʤ/, /v/, /θ/, /ð/, and /r/, suggesting EFL learners are more attentive to these sounds to improve pronunciation.